Climate change policy networks: Why and how to compare them across countries. (November 2018) - Ylä-Anttila, Tuomas; Gronow, Antti; Stoddart, Mark C.J.; Broadbent, Jeffrey; Schneider, Volker; Tindall, David B.
Abstract: Why do some countries enact more ambitious climate change policies than others? Macro level economic and political structures, such as the economic weight of fossil fuel industries, play an important role in shaping these policies. So do the national science community and the national culture of science. But the process by which such macro-structural factors translate into political power and national climate change policies can be analyzed through focussing on meso level policy networks. The Comparing Climate Change Policy Networks (COMPON) research project has studied climate change policy networks in twenty countries since 2007. Along with some findings, this paper presents some methodological challenges faced and the solutions developed in the course of the project. After a presentation of the project, we first outline some practical challenges related to conducting cross-national network surveys and solutions to overcome them, and present the solutions adopted during the project. We then turn to challenges related to causal explanation of the national policy differences, and propose Qualitative Comparative Analysis as one solution for combining different levels of analysis (macro and meso) and different data types (quantitative, network and qualitative).